1978
DOI: 10.1210/endo-103-6-1985
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Testicular Weight and Serum Gonadotropin and Testosterone Levels before, during, and after Birth in the Perinatal Rat*

Abstract: Changes in serum and pituitary LH and FSH concentrations have been measured in the newborn male rat before, during, and up to 24 h after birth. A sudden and transient increase of serum and pituitary gonadotropins is observed at birth, which is followed by a rapid increase of absolute and relative testicular weights between 2--12 h (P less than 0.0001) and by a transient increase of serum testosterone between 0 h in utero (810 +/- 26 pg/ml) and 2 h (2820 +/- 318 pg/ml; P less than 0.0001). Similarly, premature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(61 citation statements)
references
References 0 publications
4
57
0
Order By: Relevance
“…Hormone measurements were made in whole body homogenates of individual foetuses in the interest of economy instead of in pooled plasma from numerous males or females killed at each embryonic age. Studies using rats (16)(17)(18); MJ Baum, P Woutersen and AK Slob, unpublished results) have shown that the profile of sex differences in whole body androgen content parallels closely that measured in pools of plasma taken over the last week of gestation as well as over the first 24 h after birth. Using both methods male rats had significantly higher levels of androgen than females only on gestational Days El8 and El9 as well as 1 to 3 h after birth.…”
Section: Perinatal Profile Of Androgen Secretion In Ferretsmentioning
confidence: 74%
“…Hormone measurements were made in whole body homogenates of individual foetuses in the interest of economy instead of in pooled plasma from numerous males or females killed at each embryonic age. Studies using rats (16)(17)(18); MJ Baum, P Woutersen and AK Slob, unpublished results) have shown that the profile of sex differences in whole body androgen content parallels closely that measured in pools of plasma taken over the last week of gestation as well as over the first 24 h after birth. Using both methods male rats had significantly higher levels of androgen than females only on gestational Days El8 and El9 as well as 1 to 3 h after birth.…”
Section: Perinatal Profile Of Androgen Secretion In Ferretsmentioning
confidence: 74%
“…Of six litters used for this treatment group, four were bom between 10.00 and 14.00 h and were cas trated immediately after parturition, within 1-2 h of the birth of the first pup. Thus, they were castrated before the peak of the 'birth surge' of T which occurs 2 h after partu rition [32], The AVPv volumes of all of these animals (18 of the 24 castrates) were well within the range of 1 SD of the mean for the entire group of neonatally castrated males.…”
Section: Discussionmentioning
confidence: 96%
“…A neonatal surge in plasma testosterone shortly after birth has been well documented to occur in both male rats and humans [1, 2]. This increase in testosterone at a critical period of development has been implicated in the long-term modulation of a number of central nervous system (CNS) functions including play and sexual behavior, dopaminergic neurotransmission and responses to early CNS lesions [3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%